Sustainable rice-wheat cropping system in eastern India-Long term effects on soil physical conditions with integrated nutrient manag - CHAUBEY, DAYANIDHI; PATHAK, S. K.; ., SUSHANT; PRAKASH, VED; KOHLI, ANSHUMAN; DAS, ANUPAM (Journal of Soil and Water Conservation, 2018)
Decreased soil bulk density and increased aggregate stability resulted with application of inorganic fertilizers as well as N-substitution with organic materials. The soil pH was reduced from the initial value of 7.40 to 7.23 with the application of organic manures along with inorganic fertilizers. Improvement in EC value (0.37 dS m-1) as compared to their respective values (0.29 dS m-1) was recorded with 50% RDF along with 50% substitution of N through FYM. Application of organo-inorganic source of nutrients over 34 years resulted in a significant increase in soil organic carbon (SOC) content to 0.81 per cent against the initial value of 0.46 per cent with 50% RDF along with 50% substitution of N through FYM. The initial fertility status of the soil was 194 kg N, 23 kg P2O5 and 155 kg K2O ha-1. Whereas, the maximum available N (239.61 kg ha-1) as well as available phosphorus (51.15 kg ha-1) had resulted after 34 years with 50% N applied as chemical fertilizers and the remaining N substituted through FYM. Available potash (199.36 kg ha-1) was found to be maximum with 50% nutrients applied through chemical fertilizers and the remaining substituted through wheat straw, were observed after rice harvest. However, the 50% substitution of organic manures established its superiority over 25% substitutions in building up soil physical, chemical and biological properties of soil. Hence, it is concluded that substitution of 50% N either through FYM or WS or GM (Sesbania aculeata) along with 50% RDF through inorganic fertilizer is advantageous over 100% RDF for improving the soil physical conditions and fertility status.